A spatial assessment of agricultural vulnerability to climate change using multidimensional data in Maharashtra state of India - ATHARE, PRAKASH G; SINGH, DHARAM RAJ; KUMAR, NALINI RANJAN; JHA, GIRISH KUMAR; VENKATESH, P (The Indian Journal of Agricultural Sciences, 2024)
This study aims to examine district-level agricultural vulnerability in the semi-arid and drought-prone state of Maharashtra. Using a multidimensional approach, suitable indicators for 34 districts were selected under exposure, sensitivity and adaptive capacity, aligning with the IPCC 2007 framework for vulnerability assessment. The analysis used temperature and rainfall data spanning 50 years (1968–2017). It also incorporated area and yield data from 2011 to 2020, along with other indicators for the year 2019–20. The composite agricultural vulnerability index (CAVI) score was obtained using proper normalization and assigning weights. The study revealed that the Marathwada and Vidarbha regions reported higher potential crop losses. Among the districts, Sangali was the most exposed (0.57), while Jalgaon was the least exposed (0.31) to climate variations. Ahmednagar exhibited the highest sensitivity (0.70), while Nagpur showed the lowest sensitivity (0.34) to climate change. Regarding adaptive capacity, Pune demonstrated the highest resilience (0.57) and Sindhudurg displayed the lowest score (0.23). CAVI highlighted that the Konkan region, along with western Maharashtra and eastern parts of Vidarbha, exhibited relatively lower vulnerability to climate change, due to factors such as lower potential crop loss and better adaptive capacity. In contrast, Marathwada and western Vidarbha regions were more vulnerable, facing significant crop production losses and higher exposure to climate variability. Hence, to build resilience to climate change and reduce crop production losses, crop planning needs to be adjusted according to the climatic conditions in these regions.